Pregabalin misuse in a 75-year-old woman - Avinash De Sousa (Journal of Geriatric Mental Health, 2019)
Pregabalin is a drug that has been used in the management of partial epilepsy, generalized anxiety disorder, neuropathic pain, and fibromyalgia. Recently, it has found usefulness in the management of alcohol withdrawal. The use of pregabalin in the elderly is scarce, and data on the same are not easily available. We report herewith the case of pregabalin misuse in a 75-year-old woman with depression and anxiety.